2011
DOI: 10.1080/14926156.2011.570475
|View full text |Cite
|
Sign up to set email alerts
|

Which Is Greater: One Half or Two Fourths? An Examination of How Two Grade 1 Students Negotiate Meaning

Abstract: A developing body of research in classroom mathematics discourse indicates that teacher facilitation can be specific and supportive without interfering in productive student talk. Students, including those who are struggling in mathematics or lack confidence, can benefit from exploring challenging mathematics and engaging in math-talk. In this study, one teacher videotaped two academically struggling Grade 1 students engaged in a mathematical debate. Transcript analysis illustrated that the student pair used m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…A study by Siegler and colleagues (2012), for example, showed that fractions knowledge at age 10 is the strongest predictor of overall success in mathematics at age 16. Challenges with fractions can begin at an early age (Bruce & Flynn, 2011) and persist through schooling and into adulthood, both in daily activity as well as in careers where fractions misconceptions can lead to critical or even fatal errors, such as errors in dosage calculations in medical fields (Ross & Bruce, 2009;Mackie & Bruce, 2016). The stakes are high: a fragile grasp of fractions can damage and/ or limit students' school and career prospects.…”
Section: Theoretical Framingmentioning
confidence: 99%
“…A study by Siegler and colleagues (2012), for example, showed that fractions knowledge at age 10 is the strongest predictor of overall success in mathematics at age 16. Challenges with fractions can begin at an early age (Bruce & Flynn, 2011) and persist through schooling and into adulthood, both in daily activity as well as in careers where fractions misconceptions can lead to critical or even fatal errors, such as errors in dosage calculations in medical fields (Ross & Bruce, 2009;Mackie & Bruce, 2016). The stakes are high: a fragile grasp of fractions can damage and/ or limit students' school and career prospects.…”
Section: Theoretical Framingmentioning
confidence: 99%